Study protocol: biomechanical testing, finite element analysis and prospective, randomized, clinical study of single screw cephalomedullary nailing versus integrated dual interlocking screw fixation for unstable (31A21–3) intertrochanteric fractures in patients > 70 years old - Andreas Panagopoulos; Evangelia Argyropoulou; Zinon T. Kokkalis; Nicolaos Parchas; Konstantinos Tserpes (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Hip fractures are an increasingly common consequence of falls in older people that are associated with a high risk of death and reduced function. The vast majority of intertrochanteric fractures require surgical treatment to withstand early mobilization and weight bearing, which prevents complications due to prolonged bed rest and aids in fracture healing. Methods This study is compromised by two parts, the experimental study and the clinical part. In the first part, a standard 130° nail will be used with the appropriate lag screw(s) and dynamic distal locking in synthetic osteoporotic femurs and the transmission of forces in the proximal femur, measured by a cortical surface-strain distribution, will be evaluated using digital image correlation. Finite element parametric models of the bone, the nails and their interface will be also developed. Finite element computations of surface strains in implanted femurs, after being validated against biomechanical testing measurements, will be used to assist the comparison of the nails by deriving important data on the developed stress and strain fields, which cannot be measured through biomechanical testing. In the other part, will set up a prospective, randomized, comparative clinical study among the Gamma3 and IT cephalomedullary nailing, in order to investigate if there are any statistical important differences in the main radiological measurements and functional status in closed unstable intertrochanteric fractures (A21-3) in patients aged over 70 years old at the 24-week follow-up evaluation using patient reported disease-specific outcomes. Discussion This study will be the first to compare clinical, radiological and biomechanical measurements of the two different cephalomedullary nails. Our main hypothesis is that the IT nail would provide better radiological outcome and probably better clinical results than the Gama3 nail. Clinical trial registration International Standard Randomized Controlled Trial Number (ISRCTN): https://doi.org/10.1186/ISRCTN15588442 , registered on 19/4/2022.